2021
DOI: 10.1097/coc.0000000000000811
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Protocol With Limited Shoulder Range of Motion for 15 or 30 Days After Conservative Surgery for Breast Cancer With Oncoplastic Technique

Abstract: Objective: The objective is to evaluate the effect of limiting shoulder range of motion (ROM) for 15 or 30 days on surgical complications and on shoulder ROM, pain, and upper limb function of breast cancer patients following conservative oncoplastic surgery.Materials and Methods: A randomized clinical trial was conducted with 60 women with breast cancer who underwent conservative oncoplastic surgery. The day after surgery, all patients started an exercise protocol with shoulder exercises limited to 90 degrees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(51 reference statements)
0
6
0
3
Order By: Relevance
“…Most studies (39 of 57) were RCT [ 19 57 ], five were controlled non randomized clinical trials [ 58 63 ], four were prospective cohort studies [ 61 , 64 66 ], one was a retrospective cohort study [ 67 ], two was a case–control study [ 68 , 69 ], four were quasi-experimental [ 70 – 73 ], one was a pilot study [ 74 ] and one was a feasibility study [ 75 ]. The studies originated from 22 countries distributed across 4 continents (i.e., Americas, Europe, Asia and Oceania), most of which were high income countries [ 19 26 , 29 , 31 , 33 – 36 , 39 41 , 44 47 , 50 , 52 54 , 56 , 57 , 59 , 61 – 69 , 71 , 73 75 ] or upper-middle income countries [ 27 , 28 , 30 , 32 , 37 , 38 , 42 , 43 , 48 , 49 , 58 , 60 , 72 ], with only three studies conducted in lower-middle income countries [ 51 , 55 , 70 ]. The body of literature on this topic turned out to be quite recent, with 71.9% (41 of 57) of studies published between 2010 and 2022 and 22.8% (13 out of 57) between 2000 and 2009.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies (39 of 57) were RCT [ 19 57 ], five were controlled non randomized clinical trials [ 58 63 ], four were prospective cohort studies [ 61 , 64 66 ], one was a retrospective cohort study [ 67 ], two was a case–control study [ 68 , 69 ], four were quasi-experimental [ 70 – 73 ], one was a pilot study [ 74 ] and one was a feasibility study [ 75 ]. The studies originated from 22 countries distributed across 4 continents (i.e., Americas, Europe, Asia and Oceania), most of which were high income countries [ 19 26 , 29 , 31 , 33 – 36 , 39 41 , 44 47 , 50 , 52 54 , 56 , 57 , 59 , 61 – 69 , 71 , 73 75 ] or upper-middle income countries [ 27 , 28 , 30 , 32 , 37 , 38 , 42 , 43 , 48 , 49 , 58 , 60 , 72 ], with only three studies conducted in lower-middle income countries [ 51 , 55 , 70 ]. The body of literature on this topic turned out to be quite recent, with 71.9% (41 of 57) of studies published between 2010 and 2022 and 22.8% (13 out of 57) between 2000 and 2009.…”
Section: Resultsmentioning
confidence: 99%
“…Exercises targeting upper limb tissues and function were predominant. Fewer studies adopted a more global approach, providing aerobic exercises [ 21 , 23 , 52 , 66 , 71 ] or yoga [ 41 , 55 ], as well as strengthening or stretching of the lower extremity [ 19 21 ] or neck muscles [ 28 , 44 , 57 , 58 , 60 63 , 66 , 72 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, there have been some efforts to apply physical therapy and exercise in patients who underwent breast cancer surgery. Physical therapy including passive mobilization, stretching, and exercise programs introduced as early as 7 days after surgery can be effective for improvement of shoulder ROM and postoperative pain [25,26]. A randomized controlled trial showed that addition of scapular stabilization exercises and Thera-band strengthening exercises can be beneficial for shoulder function and quality of life in post-mastectomy patients with adhesive capsulitis [16].…”
Section: Discussionmentioning
confidence: 99%
“…We applied the following pragmatic search terms to identify studies; searched on 8 August 2022: {Exercise[tiab] AND shoulder[ti] AND (impairment [tiab] OR pain [tiab]) AND (("breast cancer" OR breast) AND cancer)}. We found 19 records in database searching, from which 8 records corresponded to randomised trials [28,[33][34][35][36][37][38][39]. Thus, the result of the present randomised trial is expected to have a high impact in the health system to in terms of having more focus on late-term shoulder impairments and improving the quality of physiotherapeutic rehabilitation, especially for physiotherapists involved in the management of breast cancer and late-term shoulder impairments.…”
Section: Evidence-based Researchmentioning
confidence: 99%